Domniemane wczesnośredniowieczne grodzisko w Bydgoszczy-Czersku Polskim w świetle najnowszych badań archeologicznych (Kronika Bydgoska, 2020)
This article is a summary of archeological works carried out in the area of Hutnicza Street in Bydgoszcz-Czersko Polskie in 2019. Results of field studies are preceded by presentation of the history and status of research on the site. Conclusions coming from archeological studies are completed by an analysis of available written records and analyses made by historians. Information presented in the article should help in determination of existence of a possible fortified settlement in this place during the Early Middle Ages.